Sie sind auf Seite 1von 5


Mean value theorem is one of the most important results in differential calculus,
as well as one of the most important theorems in mathematical analysis, and is
useful in proving the fundamental theorem of calculus. The mean value theorem
follows from the more specific statement of Rolle's theorem, and can be used to
prove the more general statement of Taylor's theorem. A special case of this
theorem was first described by Parameshvara (13701460) from the Kerala
school of astronomy and mathematics. The mean value theorem in its modern
form was later stated by Augustin Louis Cauchy (17891857) and Lagrange.
In general, the mean value theorem states that for a given planar arc, between
its two endpoints, there is at least one point at which the tangent to the arc is
parallel to the secant through its endpoints (as shown in figure).

Figure 1
Mean value theorem can be stated in two different ways:
1. Lagranges Mean Value Theorem
2. Cauchys Mean Value Theorem

1. Lagranges Mean Value Theorem

If f(x) be a real valued function such that (i) it is continuous in [a,b] (ii) it is
differentiable in (a,b), where a < b, then there exist at least one point c in (a,b)
such that

f(c) = {f(b) f(a)}/(b a)

or f(c)(b-a) = f(b) f(a)
Rolles theorem is a special case of this where f(a) = f(b).
Geometrically, it represents the tangent through the point c which is parallel to
the chord passing through points a and b.
The theorem can be proved by applying Rolles Theorem to a suitable function h:
[a,b]-> R such that
h(a) = h(b) and

From the figure, it is clear that h(x) is the

difference between f(x) and L(x) (L(x) is the line
joining (a, f(a)) and (b, f(b))).
So, we consider x in [a,b], then we have

Here h(x) is continuous on [a,b] , differentiable on (a,b), and
h(a)=0, h(b)=0, i.e. h(a)=h(b).
Hence by Rolles Theorem, h(c)=0 for some c in (a,b), i.e.

Hence Proved.

Another form of L.M.V.T.

Since b > a, let b=a+h
Let 0 < o < 1
s.t. c= a + oh => c= a+ o(b a)
so, f(a+ oh) = {f(a + h) f(a)}/h

f(a + h) = f(a) + hf(a + oh)

Physical Interpretation of M.V.T.

Let f: [a,b] -> R denote the distance traveled by a body from time t= a to t=
b . Then, the average speed of a moving body between two points , A at t= a,
and , B at t=b, is
Average speed = s = {f(b) f(a)}/(b a)
The mean value theorem says that there exists a time point t= c in between t=
a and t= b when the speed of the body is is actually s km/sec.

1. Following theorems are the consequence of M.V.T.
(i) Let f be differential on (a,b). If f(x) = 0 for all x in (a,b), then
f is constant on (a,b).
(ii) Let f and g be differential on (a,b). If g(x) = f(x) for all x in (a,b),
then exists a real constant C such that
g(x) = f(x) + C for all x in (a,b).
(iii) Let f be continuous on [a,b] and differentiable on (a,b).
If m, M belonging to R are such that f(x)

2. It is used to prove inequalities and approximating the square root of a natural number.
3. It is very useful in determining the monotonocity of a function, i.e. whether a is increasing
or decreasing.
4. It can be used to prove lHopitals Rule.

2. Cauchy Mean Value Theorem

Cauchy's mean value theorem, also known as the extended mean value
theorem, is a generalization of the mean value theorem.
If f(x) and g(x) are two real valued function continuous on [a,b] and both
differentiable in (a,b), then there exist at least one point c in (a,b) such that

[f(b) f(a)]g(c) = f(c)[g(b) g(a)]

Geometrically, it represents a tangent to the curve at point c which is

parallel to the secent passing through the line joining [f(a), g(a)] and
[f(b), g(b)].

Figure 3: Geometrical representation of Cauchy M.V.T.

Case I: If g(a) = g(b), we apply Rolle's Theorem to g(x) to get a point c in (a,b) such that
g(c)=0. Then
[f(b) f(a)]g(c) = f(c)[g(b) g(a)]
Case II: In the case g(a) is not equal to g(b), so we define h: [a,b]->R by

h(x) = f(x) ag(x)

where a is chosen so that h(a) = h(b), i.e.

a= [f(b) f(a)]/[g(b) g(a)]

Now applying Rolle's Theorem to h(x) gives h(c)=0, for some c in [a,b]. Thus,
h(c)= f(c) ag(c) = 0

f(c) = g(c)[f(b) f(a)] /[g(b) g(a)]

=> [f(b) f(a)]g(c) = f(c)[g(b) g(a)]
Hence Proved.